Multidimensional Views on Enterprise Information Systems Proceedings of ERP Future 2014 - Piazolo, Felix; Felderer, Michael (Lecture Notes in Information Systems and Organisation, 2016)
This volume presents the revised and peer reviewed contributions of the 'ERP Future 2014' conference held in Dornbirn/Austria on November 17 and 18, 2014. Since 2009 the ERP Future conference has been a scientific platform for research which is held each year at a different research institution. In addition to the scientific community the conference also addresses businesses developing, implementing and intensively using enterprise information systems. The research conference focusses in generally on enterprise systems and specifically on core topics such as business process management, business intelligence and enterprise resource planning systems. Submitted contributions cover the given topics from a business and a technological point of view. This combination of aspects is a unique characteristic of the conference, which results in several valuable contributions with a highly theoretical as well as practical background. .